Analysis of Factors that Influence Indonesia’s Automotive Customer Decisions towards the Repurchase of Electric Cars - Ramadhan, Muhammad Alvin Ariq; Aruan , Daniel Tumpal Hamonangan (Jurnal Samudra Ekonomi dan Bisnis, 2024)
To expand the EV ecosystem in Indonesia through consumer repurchases, it is necessary to understand what can cause consumers to repurchase electric vehicles. This research aims to determine the factors that influence consumers' decisions to repurchase electric cars in Indonesia using the application of the Extended Theory of Planned Behavior. 198 relevant respondents were selected to fill out the online questionnaire, and the collected data was then analyzed based on the SEM-PLS model. The results state that the satisfaction factor can influence consumers' positive opinions towards electric cars, resulting in interest in repurchasing electric cars. The existence of the Theory of Planned Behavior indicators along with the support of additional components in the form of monetary and non-monetary policies can also influence consumers' interest in repurchasing electric cars.